Hemispheric CSF volume ratio quantifies progression and severity of cerebral edema after acute hemispheric stroke. Issue 11 (November 2021) - Dhar, Rajat; Hamzehloo, Ali; Kumar, Atul; Chen, Yasheng; He, June; Heitsch, Laura; Slowik, Agnieszka; Strbian, Daniel; Lee, Jin-Moo
As swelling occurs, CSF is preferentially displaced from the ischemic hemisphere. The ratio of CSF volume in the stroke-affected hemisphere to that in the contralateral hemisphere may quantify the progression of cerebral edema. We automatically segmented CSF from 1, 875 routine CTs performed within 96 hours of stroke onset in 924 participants of a stroke cohort study. In 737 subjects with follow-up imaging beyond 24-hours, edema severity was classified as affecting less than one-third of the hemisphere (CED-1), large hemispheric infarction (LHI, over one-third the hemisphere), without midline shift (CED-2) or with midline shift (CED-3). Malignant edema was LHI resulting in deterioration, requiring osmotic therapy, surgery, or resulting in death. Hemispheric CSF ratio was lower on baseline CT in those with LHI (0.91 vs. 0.97, p < 0.0001) and decreased more rapidly in those with LHI who developed midline shift (0.01 per hour for CED-3 vs. 0.004/hour CED-2). The ratio at 24-hours was lower in those with midline shift (0.41, IQR 0.30–0.57 vs. 0.66, 0.56–0.81 for CED-2). A ratio below 0.50 provided 90% sensitivity, 82% specificity for predicting malignant edema among those with LHI (AUC 0.91, 0.85–0.96). This suggests that the hemispheric CSF ratio may provide an accessible early biomarker of edema severity.